Application Of Psak 101 In The Sharia Savings And Loans Cooperative Bakti Huria Syariah K.C. Parepare - Putri; Ambo Masse, Rahman; Sahrani (Islamic Financial And Accounting Review, 2022)
The purpose of this study is to determine the provisions for the presentation of financial statements and the application of PSAK 101 in KSPPS Bakti Huria Syariah K.C Parepare. This research includes qualitative descriptive research with data collection techniques carried out by observation, documentation and direct interviews with branch leaders and Admin Teller staff related to financial statements. The Interview Method is used to strengthen and deepen the study of the object under study. The focus of this research is focused on the application of PSAK 101 in KSPPS Bakti Huria Syariah K.C.Parepare based on sharia accounting principles, namely accountability, justice and truth. The results showed that the provisions for the presentation of financial statements at KSPPS Bakti Huria Syariah K.C.Parepare were not fully in accordance with PSAK 101 because KSPPS Bakti Huria Syariah K.C Parepare only recorded 3 components of financial statements, namely Balance Sheet, Profit and Loss, and Cash Flow.The application of PSAK 101 was in accordance with the principle of accountability because the data presented were concrete and real. However, it is not fully in accordance with the principles of justice and truth because the cooperative/business financial statements (Baitul Tanwil) are still combined with the social finance statements (Baitul Mall)